A retrospective study of hypofractionated radiotherapy for keloids in 100 cases - Wen, Ping (Sci Rep, 2021)
At present, the consensus on the best treatment for keloids is the combination of clinical and surgical therapies, if necessary, associated with adjuvant radiotherapy like brachytherapy. Whereas, the uniform scheme of radiotherapy in keloids is unclear. Here, we conducting a retrospective analysis to assess the efficacy and safety of a specific treatment regimen (20 Gy in 5 fractions) in keloid patients. We retrospectively analysed the medical records of keloid patients receiving auxiliary postoperative radiotherapy (PORT) treatment from 2009 to 2019. The patients were treated with the hypofractionation method of 20 Gy in 5 fractions. We compared the local control rate and complications, using the chi-square test and logistic regression analyses. After screening, we identified 100 keloid patients in this study, with a median follow-up of 59 months. In this study, the overall local control rate of keloid lesions was 84.8%. After multivariate analyses (primary keloid or not, family history, interval from surgery to irradiation and site), our research showed that primary keloid, site and interval from surgery to irradiation were significantly related to recurrence. Acute radiation injury and late radiation injury accounted for 3% (erythema) and 1% (skin sclerosis) of the total cases, respectively. Our results indicate that a postoperative hypofractionation with radiation dose of 20 Gy in 5 fractions may be effective, easy to accept and safe for keloid patients.